Steam pasteurization of beef carcasses - D.E. Schafer; R.K. Prasai; Abbey L. Nutsch; Randall K. Phebus; John R. Wolf; John A. Unruh; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1996)
This research evaluated the effectiveness of a newly patented steam-pasteurization process for reducing bacterial populations on the surfaces of freshly slaughtered beef carcasses. The process was developed jointly by Frigoscandia Food Processing Systems (Bellevue, WA) and Excel Corp. (Wichita, KS), a division of Cargill (Minneapolis, MN). In laboratory studies, portions of prerigor beef carcasses inoculated with very high levels of three pathogens, Salmonella, Escherichia coli O157:H7, and Listeria, were treated in a prototype steam-pasteurization chamber, which effectively eliminated at least 99.9% of all three pathogens and was most effective when used in combination with other standard commercial decontamination methods. The effectiveness of a full-scale, automated, steam-pasteurization system was evaluated in a commercial beef slaughter facility. The commercial system was very effective, reducing the naturally occurring overall bacterial population by over 90% and reducing the population of E. coli (nonpathogenic) and related organisms to undetectable levels. Steam pasteurization is very effective at reducing bacterial contamination on unchilled beef carcasses and should be viewed as one step in an overall process of reducing the risk of pathogenic bacteria in beef and beef products.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Steam pasteurization; Slaughter; Beef safety; E. coli O157:H7